What are the forms of crimes against the Unitary State of the Republic of Indonesia in the Penal Code? A Book Review 'Kejahatan terhadap Negara Kesatuan Republik Indonesia', Adami Chazawi & Ardi Ferdian, Sinar Grafika, 186 Pages, ISBN 978-979-007-771-3 - Lembang, Alviona Anggita Rante (Indonesian Journal of Advocacy and Legal Services, 2020)
Criminal Acts against State Security in Chapter I of Book II of the Penal Code (KUHP), are criminal groups that protect the legal interests regarding national safety and security of the Unitary State of the Republic of Indonesia. The forms of crimes against state security, which are protected by the provisions of Chapter I of Book II, are fundamental legal interests of the life process of the state in Indonesia. From the condition of preserving legal interests is an important factor in efforts to bring the Indonesian people to a comfortable and peaceful, justice, and prosperous life which is the goal of establishing the Unitary State of the Republic of Indonesia in 1945. Since the Indonesian nation's independence and sovereignty, there have been repeated incidents of attacks and rape in the interests of the life law of the nation and state of the Republic of Indonesia., such as the first PKI rebellion (MUSO in Madiun 1948); Kartosuwiryo in West Java (1949); PRRI in Sumatra (1958); PERMESTA in Sulawesi (1957); RMS in Maluku (1950); the second betrayal of the PKI (30-S / PKI); and there is still no end to interference with the population of Papua by the Free Papua Separatists.Criminal Law in Chapter I of Book II of the Penal Code is a legal instrument as a preventive and repressive tool to fight and overcome rape / attacks on the interests of the national law, security and safety of the Republic of Indonesia.